Resultados del trabajo de los estudiantes para el desarrollo de objetos virtuales en el tema de dilatación - Mejía Cortes, Gustavo Antonio (Revista Científica, 2011)
﻿The subject of Fluids and Thermodynamics for engineering majors at Pontificia Universidad Javeriana includes the topic of thermal expansion, because this phenomenon influences many properties of materials, since changing the dimensions of a body affects its density, moment of inertia , electrical resistivity, among others. Students find it difficult to tackle problems or exercises on this topic, particularly when dealing with objects that have holes or gaps, or when expansion generates displacements or shape changes. During the semester I-2009, we ask our students, as small group work, to develop a Virtual Learning Object (VLO) related to thermal expansion, in order to use it as teaching aid in future academic terms. Each VLO should focus on the solution of a single problem and it was expected such VLOs would improve understanding by new students approaching the subject. Some VLOs obtained as a result of this project have in fact been used in following semesters. We have concluded that having students solve problems and apply results to develop Virtual Learning Objects is a useful strategy to improve the quality of explanations and insight about these issues. It also contributes to graphical visualization.